Correlation between Tumour Associated Macrophage (TAM) Infiltration and Mitotic Activity in Canine Soft Tissue Sarcomas - Riccardo Finotello; Kate Whybrow; Giulia Scarin; Lorenzo Ressel (Animals, 2021)
Tumour-associated macrophages (TAMs) are an important part of the tumour microenvironment but knowledge of their distribution in canine soft tissue sarcomas (STSs) is limited to absent. We analysed 38 STSs retrieved from the veterinary pathology archive; oral and visceral STSs, synovial cell sarcoma, tumours of histiocytic origin, haemangiosarcoma, carcinosarcomas, and undifferentiated tumours were excluded. Iba-1 positive, non-neoplastic tumour infiltrating cells (morphologically indicative of macrophages) were classified as TAMs and were counted in 10 consecutive tumours areas, where no necrosis or other inflammatory cells could be identified. Associations between numbers of TAMs and mitoses, differentiation, and necrosis scores or grade were investigated. TAMs were evident in all STSs and ranged between 6% to 62% of the cells in the microscopic field. The number of TAMs positively correlated with the STSs’ histologic grade. When the components of the grade were analysed separately, TAMs were statistically correlated with mitoses, but not with differentiation or necrosis score. The present findings suggest that TAMs are present in higher numbers when STS proliferation is the predominant feature that drives tumour grade. The abundant presence of TAMs in high-grade STSs may also increase the likelihood of a pathologist misdiagnosing STS for histiocytic sarcoma.